Peran Pemerintah Dalam Program Pemberdayaan Remaja Di Desa Milangodaa Barat Bolaang Mongondow Selatan - Toi, Adrian; Gobel, Lisda Van; Bakari, Luthfia (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This study aims to determine the role of the Government in the youth empowerment program in Milangodaa Barat Village, Tomini District, South Bolaang Mongondow Regency. The research method uses a descriptive type with a qualitative approach. Data collection techniques are carried out through observation, in-depth interviews with a number of informants, and documentation.The results of the study that: seen from the role of the government as a motivator is still not optimal in motivating and involving teenagers in various activities in the village, this shows the low level of youth participation. Then the role of the government as a communicator is also still less effective due to limited sources of information and lack of socialization of programs related to village design. Seen from the role of the government as a facilitator is still inadequate because the available facilities are still limited. Teenagers hope that the village government will immediately add the facilities needed, such as badminton and takraw courts. It is recommended that the government increase efforts to motivate and involve teenagers in the planning and implementation process of activities in the village. The need to increase transparency and openness of information by more actively conveying village programs and plans. The need to accelerate the realization of the addition of badminton and takraw courts to help teenagers develop their potential and talents in these sports.